OPEN DATA AND ARTIFICIAL INTELLIGENCE: A COMPARATIVE ANALYSIS OF THE USA AND CHINA - Aitenov Н.Ж.; Kulambayev Б.О.; Zhekenov Д.К.; Gubina Д.И. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
The purpose of this study is to examine the openness of big data practices among major IT companies in the United States and China, with an emphasis on their implications for the development of artificial intelligence and international cooperation. The study employed a qualitative analysis framework incorporating case studies to evaluate data availability, transparency, and collaborative initiatives. The findings indicate that American companies such as Microsoft and Google exhibit higher levels of data openness, supported by a regulatory environment that balances innovation with privacy protection. In contrast, Chinese companies like Tencent and Alibaba prioritize internal data use under stringent regulatory control, emphasizing data security and sovereignty. These differences pose challenges for international cooperation in the field of artificial intelligence, exacerbated by geopolitical tensions and divergent regulatory landscapes. Despite these barriers, there are opportunities for harmonization through common frameworks and collaborative initiatives aimed at leveraging collective expertise to advance AI technologies globally.